2007
DOI: 10.1562/2006-03-17-ra-850
|View full text |Cite
|
Sign up to set email alerts
|

Phytochrome-Mediated Inhibition of Coleoptile Growth in Rice: Age-dependency and Action Spectra†

Abstract: Phytochrome has been shown to be the major photoreceptor involved in the photo-inhibition of coleoptile growth in Japonica-type rice (Oryza sativa L.). We have characterized this typical photomorphogenetic response of rice using mutants deficient in phytochrome A (phyA) and phytochrome B (phyB) and with respect to age-dependency and action spectra. Seedlings were irradiated with a pulse of light 40 h or 80 h after germination (i.e. at an early or late developmental stage) and the final coleoptile length of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
23
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 25 publications
2
23
1
Order By: Relevance
“…At the early stage of development [40 h after inducing germination (AIG)], photoinhibition was predominantly due to the phyB-mediated low-fluence response (LFR), but at the late developmental stage (80 h AIG), it consisted of the phyA-mediated very lowfluence response (VLFR) as well as the phyB-mediated LFR. 3,4 In the case of root growth, the sensitivity of photoinhibition also depended on age, and was most sensitive in the period of 48-96 h AIG when seedlings were irradiated for 24 h. Using rice phytochrome mutants, 5 we found that far-red light for root growth inhibition was perceived exclusively by phyA, that red light was perceived by both phyA and phyB, and that phyC had little or no role in growth inhibition. Furthermore, the fluence rate required for phyB-mediated inhibition was more than 10,000-fold greater than that required for phyA-mediated inhibition.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…At the early stage of development [40 h after inducing germination (AIG)], photoinhibition was predominantly due to the phyB-mediated low-fluence response (LFR), but at the late developmental stage (80 h AIG), it consisted of the phyA-mediated very lowfluence response (VLFR) as well as the phyB-mediated LFR. 3,4 In the case of root growth, the sensitivity of photoinhibition also depended on age, and was most sensitive in the period of 48-96 h AIG when seedlings were irradiated for 24 h. Using rice phytochrome mutants, 5 we found that far-red light for root growth inhibition was perceived exclusively by phyA, that red light was perceived by both phyA and phyB, and that phyC had little or no role in growth inhibition. Furthermore, the fluence rate required for phyB-mediated inhibition was more than 10,000-fold greater than that required for phyA-mediated inhibition.…”
mentioning
confidence: 91%
“…3 In this study, we examined photoinhibition of seminal root growth, and found similarities and differences between light-induced growth inhibition of the two organs in rice seedlings. Although coleoptile growth was inhibited by pulses of light, growth inhibition of seminal roots required light irradiation longer than 6 h. The Bunsen-Roscoe law of reciprocity was not observed in the growth inhibition of seminal root.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Several photoreceptor genes have been identified in rice plants that included phytochromes (OsPHYA, OsPHYB, OsPHYC [Takano et al 2001), cryptochromes (OsCRY1a, OsCRY1b, OsCRY2 [Hirose et al 2006;Zhang et al 2006]), and phototropins (OsPHOT1a, OsPHOT1b, OsPHOT2 [Jain et al 2007;Goh et al 2009]). PHYA and PHYB were involved in the photoinhibition of rice coleoptile elongation (Xie et al 2007), and they also participated in the signal transduction of light-induced root coiling in high-nitrogen conditions (Shimizu et al 2009). PHYA, CRY1a, and CRY1b have been found to be involved in the regulation of jasmonate biosynthetic enzymes such as allene oxide synthase (AOS) in rice plants (Haga and Iino 2004;Hirose et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…The recent generation and characterization of phytochrome single, double, and triple mutants have revealed that phyB plays important roles in seedling de-etiolation, flowering, and fertility in rice (Takano et al 2005;Xie et al 2007;Takano et al 2009). In addition to its roles in photomorphogenesis, we have recently observed that phyB-mediated light signal affects resistance to Magnaporthe grisea and drought tolerance in rice (Xie et al 2011;Liu et al 2012).…”
Section: Introductionmentioning
confidence: 99%